2009
DOI: 10.1159/000235248
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Outcomes between Spousal Transplants and Other Living Unrelated Donor Transplants: Single-Center Experience

Abstract: Background/Aims: The greater use of living unrelated donors (LUDs) as kidney donors is a worldwide trend in the current era of organ shortage, and spouses are an important source of LUDs. This study was to compare the long-term outcomes of spousal donor grafts with other LUD grafts. Methods: Among 445 LUD grafts, 77 were spouses and 368 were other LUDs. The clinical characteristics and long-term survival rates for spousal transplants were compared with those for other LUD transplants, and risk factors affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(26 reference statements)
0
8
1
Order By: Relevance
“…This is in contrast to previously published studies, where the incidence of an acute allograft rejection has been found to be slightly more in SD transplants as compared to RD transplant[124791013151619] although the difference has been found to be statistically significant in only one study. [10] One study[8] has found that recipients of SD transplants are significantly more likely to have early acute allograft rejection as well as more severe rejection.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to previously published studies, where the incidence of an acute allograft rejection has been found to be slightly more in SD transplants as compared to RD transplant[124791013151619] although the difference has been found to be statistically significant in only one study. [10] One study[8] has found that recipients of SD transplants are significantly more likely to have early acute allograft rejection as well as more severe rejection.…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, another study[1] has reported graft function in SD transplant recipients to be significantly inferior at the end of the follow-up period when compared to RD transplant group. In other studies[2478911151619] however, graft function was similar in the two groups. Possible reasons for the contrasting results are:…”
Section: Discussionmentioning
confidence: 57%
“…First, spouse donors are not limited by legal and ethical problems. Second, the graft outcome from a spouse donor is as good as from an LRD [9,10] or other LUDs [11]. Third, in a nuclear family system, it is natural to prefer one's spouse as an organ source to other familial members.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of more effective immunosuppressive medication and an expanding experience regarding AB0-incompatible transplantation, also genetically unrelated living donors are able to donate a kidney ( 6 , 7 ). In Germany, a close relationship between donor and recipient is mandatory.…”
Section: Introductionmentioning
confidence: 99%
“…Altruistic or anonymous donation is legally not allowed. Spouses, which seem to be as suitable as other genetically unrelated living donors ( 7 , 8 ), represent a large group of organ donors. Due to their close relationship to the recipient, often living in the same household, they experience the consequences of ESRD first hand.…”
Section: Introductionmentioning
confidence: 99%